A reducing of a chaotic movement to a periodic orbit, of a micro-electro-mechanical system, by using an optimal linear control design - Chavarette, Fábio Roberto; Balthazar, José Manoel [UNESP]; Felix, Jorge L. P. [UNESP]; Rafikov, Marat (Elsevier B.V., 2009)
This paper analyzes the non-linear dynamics. with a chaotic behavior of a particular microelectro-mechanical system. We used a technique of the optimal linear control for reducing the irregular (chaotic) oscillatory movement of the non-linear systems to a periodic orbit. We use the mathematical model of a (MEMS) proposed by Luo and Wang. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Non-linear dynamics; Micro-electro-mechanical system; MEMS; Optimal linear control